"Un-forming" fibre-steered preforms: Towards fast and reliable production of complex composites parts. (10th November 2021) - Sun, Xiaochuan; Belnoue, Jonathan P.-H.; Wang, Wei-Ting; Kim, Byung Chul; Hallett, Stephen R.
Abstract: Automated Fibre Placement (AFP) allows for efficient deposition of composite prepreg materials at large scale in a reliable and reproducible way, while keeping human effort to a minimum. However, the technique is not perfectly suited to manufacturing small/medium parts with complex geometries. Deviation between as-designed and as-manufactured parts is almost inevitable, as is the occurrence of process-induced defects. In this study, an alternative design and manufacturing process is proposed. Instead of depositing composite tapes directly onto the complex mould, a flat tailored preform made from steered fibre tows is created first, and then the flat preform is subsequently formed into a 3D complex shape. The fibre path in the flat tailored preform is derived from a new virtual 'un-forming' process of a complex 3D part design with target fibre paths. To demonstrate the process, a small doubly curved composite part was un-formed. Fibre-steered tailored preforms were created using the continuous tow shearing (CTS) technique and then formed into the target shape using double diaphragm forming. The as-manufactured part was compared with the as-designed part as well as a part manufactured from straight fibre prepreg. The results demonstrated the feasibility of the virtual un-forming process and the potential of proposed manufacturing route. Graphical abstract: Image 1